Economic and technical reconstruction in Central Europe : delivered at a meeting of the Austrian engineers on july 12th, 1943 - Nemec, Frantisek (London : Association of Austrian Engineers, Chemists and Scientific Workers in Great Britain, 1943)
Bibliotheek Camille Huysmans
Frantisek Nemec was minister in de Tsjechische regering in ballingschap in Londen
Engels
Brochure
Keywords: wederopbouw; Centraal Europa